Landform Control On Settlement Distribution Pattern in Progo Delta, Indonesia - Suprapto Dibyosaputro (Faculty of Geography, Universitas Gadjah Mada, 2015)
Landform is part of the Earth ‘s surface whose characteristics affect resources and geomorphological hazard, and therefore, affect humans in determining their choices in building settlements. This research aims to : ( 1 ) analyze landforms control on settlement distribution pattern in abandoned Progo Delta, and ( 2 ) analyze the factors that influence humas in choicing their residental locations. Landform control on the settlement distribution was analyzed from produced geomorphological and settlement maps and overlay them. The influence factors were analyzed from the results of in-depth interviews conducted in each village in the study area. The results show that the settlement in the study area is distributed in a dispersed pattern, following the presence of abandoned delta’s natural levees. The influencing factors include flat topography that implies a good accessibility, soil fertility that defines land capability in sustaining their life, water resource availability, and security from disasters especially floods.